Myricitrin Alleviates Oxidative Stress-induced Inflammation and Apoptosis and Protects Mice against Diabetic Cardiomyopathy - Zhang, Bin (Sci Rep, 2017)
Diabetic cardiomyopathy (DCM) has been increasingly considered as a main cause of heart failure and death in diabetic patients. At present, no effective treatment exists to prevent its development. In the present study, we describe the potential protective effects and mechanisms of myricitrin (Myr) on the cardiac function of streptozotosin-induced diabetic mice and on advanced glycation end products (AGEs)-induced H9c2 cardiomyocytes. In vitro experiments revealed that pretreatment with Myr significantly decreased AGEs-induced inflammatory cytokine expression, limited an increase in ROS levels, and reduced cell apoptosis, fibrosis, and hypertrophy in H9c2 cells. These effects are correlated with Nrf2 activation and NF-κB inhibition. In vivo investigation demonstrated that oral administration of Myr at 300 mg/kg/day for 8 weeks remarkably decreased the expression of enzymes associated with cardiomyopathy, as well as the expression of inflammatory cytokines and apoptotic proteins. Finally, Myr improved diastolic dysfunction and attenuated histological abnormalities. Mechanistically, Myr attenuated diabetes-induced Nrf2 inhibition via the regulation of Akt and ERK phosphorylation in the diabetic heart. Collectively, these results strongly indicate that Myr exerts cardioprotective effects against DCM through the blockage of inflammation, oxidative stress, and apoptosis. This suggests that Myr might be a potential therapeutic agent for the treatment of DCM.